Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Hasil Belajar - Endang Lovisia (SPEJ (Science and Physic Education Journal), 2018)
The research aims at finding out the significance influence of guided inquiry on students physic achievement. It was an experiment research by group comparison. The population was all of the tenth grade students of SMA Negeri 6 Lubuklinggau. The samples was collected by cluster random sampling with grade X1 as experiment class treated with guided inquiry and X2 as control class treated with lecturing method. Technique for collecting data was through test analysis. Based on the posttest result with level of confidence 5% it was find out that t obtained = 2,61 and ttabel = 2,02 because t obtained > ttabel. Therefore, it can be concluded that there was a significant effect of guided inquiry model on Student physic achievement at the tenth grade of SMAN 6 Lubuklinggau. Keywords : Physic, Students' achievement, Guided Inquiry